Assessment of Knowledge, Attitude, and Practice of Therapeutic Drug Monitoring Among Hospital Pharmacists in Saudi Arabia - Sharaf E. Sharaf; Abdulhamid Dahlawi; Abdulrahman Alhajjaji; Afnan Alqurashi; Mmyada Albarakati; Mustafa Badawi; Nouf Alhassani; Omar Alshareef; Sultan Bajawi; Walid Alsufyani; Widad Alfahmi; Yomna Qudus; et al. (International Journal of Clinical Practice)
Conclusion: As a lack of TDM knowledge directly contributes to reduced practice levels, increasing TDM knowledge and practice by introducing more intensive pharmaceutical programs that illustrate TDM clinical applications in hospitals is recommended, which will enhance HP integration.